War Studies Reader : From the Seventeenth Century to the Present Day and Beyond. - Sheffield, Gary (Continuum International Pub. Group, 2010)
ThisÈreader will provide authoritative and thought-provoking pieces of War Studies scholarship in an accessible form. Coveringä wide spectrum of topics, including strategy (Colin S. Gray), 'Shell-Shock and the Cultural History of the Great War' (Jay Winter) and Coalition Warfare (Holger H. Herwig), this book purposefully ranges across military history, international relations and contemporary security to capture the multidisciplinary nature of the subject.ÈGary Sheffield also provides an introduction to the Reader and to War Studies, explaining the growth and development of thi.